Sistem Monitoring Pengadaan Bahan Baku Menggunakan Metode Extreme Programming Pada Ayam Geprek Family - Fitrianti; Yohana Dewi Lulu Widyasari (ABEC Indonesia, 2022)
Ayam Geprek Family is one of the fast-food businesses. This business was founded in 2019 and is in Tanah Putih Tanjung Melawan. Ayam Geprek Family uses a make-to-stock business strategy, i.e., production will still be carried out without an order. Inventory of raw materials is important and very influential in the smooth production process. The condition of the high production volume has not been supported by the calculation of the optimal use of raw materials, resulting in several impacts. The main impact of the excess is the high cost of storage. On the other hand, the capital allocation for other investments cannot be done optimally. As well as the reduced quality of raw materials that are stored for too long. Therefore, handling and control are needed that can assist in monitoring the procurement of raw materials. The development of this procurement monitoring system uses material requirements planning (MRP) and forecasting techniques. System development using extreme programming (XP) approach. This research produces a system that can display information on planning and ordering raw materials in schedules and notifications to make monitoring easier. The time for system development using extreme programming becomes more effective and efficient, which is approximately 3 months. In black box testing, the system can run 100% of all features. In white box testing, the results of the Cyclomatic Complexity calculation are 18 regions for the MRP program algorithm.